Changing activity in the construction sector in selected states 2003-2012 - Rafał Wolski; Magdalena Załęczna (e-Finanse: Financial Internet Quarterly, 2017)
Construction companies are important economic actors in every country. Their activity translates into employment levels, tax revenues, and the provision of new spaces that require further expenditure on equipment, thus stimulating consumer spending. The activity of construction companies depends on the demand for space, the state of the economy and the financial market. Undoubtedly economic disturbances in the form of a recession have a significant impact on construction activity. The authors were interested in whether the boom and recession in the selected countries were similarly reflected in the activity of construction companies. In particular, they were interested in residential construction activity, although it was not possible to select companies that would only deal with residential construction. The authors selected four post-socialist countries and two countries which are called winners of the integration process due to their enormous economic growth.
Keywords: D22; L25; R30; 330; companies; residential real estate; profitability